Cambridge Young Learners English Tests : Movers - Cliff, Petrina (New York Oxford University Press, 2010)
Four full-colour practice tests for the Cambridge English: Movers level.
Include Illustration
Keywords: English language -- English language--Study and teaching (Elementary)--Foreign speakers